Linking Innovative Potential to SME Performance: An Assessment of Enterprises in Industrial South Wales - Rick Delbridge; Tim Edwards; Max Munday (European Regional Science Association (ERSA), 2001)
The attraction of inward investment from the UK and from overseas was the main focus of regional development policy in Wales for much of the 1970s and 1980s. Whilst Wales has been particularly successful in attracting foreign enterprise, the contribution of new investors to improving longer term regional economic prospects has been questioned at several levels. With concerns over inward investor stability, embeddedness, and contribution to local value added, increasing weight has been given to the encouragement, and development of innovative indigenous SMEs in the Welsh economy. General and sectoral initiatives to encourage SME development and innovation in Wales have also taken place against a background of historically low levels of new firm formation in the region, together with the presence of factors expected to hinder SME growth including low levels of capital availability. Ultimately, it is hoped that a strongly performing indigenously controlled and innovative SME sector will go some way to improving regional growth prospects, and hence play a role in reducing the GDP per capita gap between Wales and the UK. During the 1990s a series of research and consultancy studies in Wales have been undertaken seeking to audit SME activities, define needs and identify market failures in provision of information and services. These have formed the basis of revised policy and then for new resource directions emanating at the European, regional and local levels. Encouraging innovative activity has been at the forefront of the network of initiatives currently underway in Wales. New initiatives have often been instituted without a clear appreciation of the nature of innovation, and how innovative activities link to innovative outputs and then feed through to improved business performance. This paper examines the link between innovative activity, outcomes and the performance of SMEs in Wales. A range of European, UK and locally developed initiatives in Wales seek to encourage innovative activity in indigenous SMEs. However, it is the contention of this paper that these initiatives have often been instituted without a clear appreciation of how, if, and which innovative activities feed through to improved business performance. The paper offers a general method of assessing the innovative potential (the configuration of management practices, capabilities, internal and external linkages facilitating the generation of appropriation of ideas) of manufacturing SMEs. This then leads on to an examination of how far innovative potential is connected to operational and general business performance. The paper describes how the model was developed and used to assess the innovative potential of a sample of manufacturing SMEs in Industrial South Wales, and how far the innovative potential can be linked to improved operational and business performance. The introduction to the paper reviews current literature on innovation in SMEs, and demonstrates how far recent studies have succeeded in measuring, and then linking innovative inputs of SMEs to innovative outputs and firm performance. The second section builds upon the review to develop a working model of an innovative SME. Innovation is considered not only in terms of new product or process development but more generally as practice. The model reveals the innovative firm as one that identifies, interprets, and applies knowledge effectively, and as appropriate throughout the organisation. The model described represents a synthesis of previous research. Key factors in the model include strategy and the techniques and practices deployed to facilitate the development and appropriation of ideas for innovation. Broadly this focuses on SME commitment to innovation, and management practices supporting this commitment. The third section describes how the model was operationalised into an auditing tool, and then used to assess the innovative potential of a sample of manufacturing SMEs in Industrial South Wales. The fourth section summarises the results from the initial research programme, and in particular, considers whether the unique operating structures usually associated with SMEs hinder or facilitate the adoption of new structures for organisational learning. Moreover the section examines whether the existence of certain configurations of practices coincide with improved business performance and operational efficiencies. The conclusions consider these results in the context of the directions being adopted by current regional SME policy initiatives in Industrial South Wales.
Keywords: 330